Mangrove community structure, aboveground biomass, and carbon sequestration in the unprotected coastal areas of Sta. Cruz, Davao del Sur, Philippines - GLE LIEZL C. SANTE; DRAHCIR E. UBAT; MAREN M. PENDON; JAYSON R. PUCOT (Society for Indonesian Biodiversity, 2026)
Abstract. Sante GLC, Ubat DE, Pendon MM, Pucot JR. 2026. Mangrove community structure, aboveground biomass, and carbon sequestration in the unprotected coastal areas of Sta. Cruz, Davao del Sur, Philippines. Biodiversitas 27 (5): d270507. https://doi.org/10.13057/biodiv/d270507. Mangrove ecosystems are vital for carbon sequestration and climate change mitigation, yet their ecological functions within fragmented, unprotected margins remain understudied. This study provides the first integrated evaluation of mangrove community structure, aboveground biomass (AGB), and carbon stocks in the unprotected coastal zones of Sta. Cruz, Davao del Sur, Philippines. A total of 36 plots (10×10 m) were established across four barangays for vegetation assessment. Five mangrove species from three families were recorded, indicating substantially lower species richness compared to nearby protected areas. The community was numerically dominated by Avicennia marina (67.80% relative abundance), while Sonneratia alba, despite its low abundance, contributed the highest aboveground biomass (217.15 Mg/ha) and carbon stock (104.23 MgC/ha). Total estimated stand aboveground biomass and carbon stock were 519.33±75.57 Mg/ha and 249.27±36.28 MgC/ha, respectively. Diversity was highest in Brgy. Tuban (H′: 1.04, J′: 0.94), reflecting a relatively balanced species distribution despite low overall richness. Crucially, while the area retains significant blue carbon capacity driven by mature legacy trees, it suffers from structural imbalance and depleted biodiversity. This underscores the urgent need for strategic conservation interventions, including mixed-species restoration and the strict protection of mature stands, and their integration into local coastal management frameworks to enhance both biodiversity and climate mitigation functions.